Reduced Toll-Like Receptor 3 Expression in Chronic Hepatitis B Patients and Its Restoration by Interferon Therapy. Issue 7 (October 2013) - Huang, Yi-Wen; Lin, Shih-Chang; Wei, Shu-Chen; Hu, Jui-Ting; Chang, Han-Yu; Huang, Shih-Hung; Chen, Ding-Shinn; Chen, Pei-Jer; Hsu, Ping-Ning; Yang, Sien-Sing; Kao, Jia-Horng
Background: Toll-like receptor (TLR)3 gene variants may correlate with clinical significance of chronic viral infections including HBV. We aimed to investigate the expression of TLR3 in peripheral blood mononuclear cells (PBMCs) and liver cells of chronic hepatitis B (CHB) patients and its response to pegylated interferon or nucleoside analogue therapy. Methods: We consecutively enrolled 127 CHB patients and 64 hepatitis B surface antigen-negative, anti-HCV-negative healthy individuals as controls. We compared the TLR3 expressions on fresh PBMCs and liver cells from patients and controls, before and during pegylated interferon or nucleoside analogue therapy. Results: Compared to controls, patients had a lower TLR3 mean fluorescence intensity (MFI) on PBMCs (mean ±sd 14.61 ±13.49 versus 9.70 ±4.61; P <0.001), independent of age, gender and alanine aminotransferase (ALT; -13.466, 95% CI -17.202, -9.730; P <0.001). Patients had limited TLR3 stains on Kupffer cells, whereas controls had diffuse stains on Kupffer and hepatocytes. Hepatic TLR3 messenger RNA was lower in patients than controls (0.47 ±0.30 versus 1-fold). Using pretreatment TLR3 MFI as a referent, among 5 of 12 pegylated-interferon-treated patients with sustained virological response (SVR), TLR3 MFI was restored to a mean of 1.5- to 1.7-folds immediately after treatment. Among seven non-responders or relapsers, TLR3 MFI reduced to a mean of 0.5- to 0.7-fold. Among 10 entecavir-treated patients with on-treatment virological response, TLR3 MFI gradually was restored to a mean of 1.2-folds during 48-week therapy. Conclusions: CHB patients have reduced TLR3 expression on PBMCs, independent of age, gender and ALT, and on liver cells. Patients with pegylated-interferon-induced SVR have a more significant restoration of TLR3 expression than those under entecavir.